Mesoporous carbon aerogel with tunable porosity as the catalyst support for enhanced proton-exchange membrane fuel cell performance. (March 2021) - Gu, K.; Kim, E.J.; Sharma, S.K.; Sharma, P.R.; Bliznakov, S.; Hsiao, B.S.; Rafailovich, M.H.
Abstract: Proton-exchange membrane fuel cells (PEMFCs) are considered to be one of the most promising clean technologies to mitigate climate change, air pollution, and energy crisis. Although PEMFCs have been intensively investigated over the past five decades, the relatively low current density, high cost, and poor durability remain as obstacles to full commercialization. In this study, we present the development and the application of a porosity-tunable carbon aerogel (CA) as an alternative to the carbon support in the PEMFC to overcome its technical barriers. CA demonstrates highly tunable mesopore volume and surface area. The N2 isotherm with non-localized density functional theory analysis shows the optimized CA had extremely high mesopore volume, which was 4.26 times larger than the traditional carbon support (i.e., Vulcan XC-72R). Transmission electron microscopy shows a better catalyst (i.e., platinum nanoparticles) distribution on the CA support. This even distribution of platinum nanoparticles significantly enhances the catalyst utilization of the electrodes in our cyclic voltammetry analysis. It also contributes up to a 713% higher specific power density in our fuel cell testing. The standard accelerated stress tests exhibit that CA has excellent durability compared with the conventional carbon support. Thus, the mesoporous CA provides an efficient and durable alternative to existing carbon material as a catalyst support in PEMFCs. Graphical abstract: Image 1 Highlights: The electrochemical surface area and Brunauer-Emmett-Teller surface area of CA-200 are 2.2 and 2.7 times larger than Vulcan XC-72R, respectively. Using CA-200 in the proton-exchange membrane fuel cell increased power output by up to 713% under various environments. CA-200 exhibited enhanced durability after 10k cycles of DOE2020 accelerated stress tests.